The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00246-018-2046-x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive left ventricular dysfunction and myocardial fibrosis in Duchenne and Becker muscular dystrophy: a longitudinal cardiovascular magnetic resonance study

Abstract: We thank Drs. Yukitoshi Isikawa and Yuka Ishikawa for providing DMD/BMD specific knowledge and insight and Kinya Ishizaka for technical assistance. This study was funded by the Miyata Cardiac Research Promotion Foundation (to T.A.). The funder had no role in the study design, data collection, analysis, interpretation of data, or in the writing of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Other observational studies suggest it is unclear if the progressive decline in LV function that characterizes DMD cardiomyopathy can be attenuated by ACEI and/or BB. Aikawa et al 7 reported that fibrosis, as measured by late gadolinium enhancement with CMR, was not attenuated by ACEI, and that only subjects with a reduced LVEF at baseline exhibited an increase in LVEF with therapy 7 . Similarly, Hor et al 11 found that the addition of an ACEI to chronic steroid therapy did not reduce the decline of LV circumferential strain as measured by CMR.…”
Section: Resultsmentioning
confidence: 99%
“…Other observational studies suggest it is unclear if the progressive decline in LV function that characterizes DMD cardiomyopathy can be attenuated by ACEI and/or BB. Aikawa et al 7 reported that fibrosis, as measured by late gadolinium enhancement with CMR, was not attenuated by ACEI, and that only subjects with a reduced LVEF at baseline exhibited an increase in LVEF with therapy 7 . Similarly, Hor et al 11 found that the addition of an ACEI to chronic steroid therapy did not reduce the decline of LV circumferential strain as measured by CMR.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were included in our meta-analysis ( Duboc et al, 2005 ; Jefferies et al, 2005 ; Kajimoto et al, 2006 ; Rhodes et al, 2008 ; Matsumura et al, 2010 ; Viollet et al, 2012 ; Raman et al, 2015 ; Silva et al, 2017 ; Aikawa et al, 2019 ; Adorisio et al, 2019 ; Dittrich et al, 2019 ; Kim et al, 2020 ). Four studies were RCTs, ( Duboc et al, 2005 ; Raman et al, 2015 ; Silva et al, 2017 ; Dittrich et al, 2019 ) seven were observational, ( Jefferies et al, 2005 ; Kajimoto et al, 2006 ; Rhodes et al, 2008 ; Viollet et al, 2012 ; Adorisio et al, 2019 ; Aikawa et al, 2019 ; Kim et al, 2020 )and one study was open-label. Study characteristics are summarized in Table 1 ( Matsumura et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…12 Both readers were blinded to clinical information. The extent of LGE was expressed as a percentage of LV mass using a 5-standard deviation (SD) threshold above the mean of normal myocardium 3 because the extent of LGE on PSIR sequence quantified using the "n"-SD method has been reported to be comparable to that on inversion-recovery balanced steadystate free precession sequence in both ischemic and nonischemic cardiomyopathies. 13 Global ECV was calculated using pre-and post-contrast T 1 values of myocardium and blood pool (T 1 myo pre , T 1 myo post , T 1 blood pre , and T 1 blood post , respectively) as follows: ECV (%) = (1 − hematocrit) × (1/T 1 myo post − 1/T 1 myo pre )/(1/T 1 blood post − 1/T 1 blood pre ).…”
Section: Methodsmentioning
confidence: 99%
“…1 The most common form of cardiac involvement in muscular dystrophy is dilated cardiomyopathy, 2 presenting as an age-related progression of left ventricular (LV) dysfunction and myocardial fibrosis detected by late gadolinium enhancement (LGE) cardiovascular MR (CMR) imaging. 3 Accurate evaluation of myocardial fibrosis could be useful for risk stratification 4 and determining early initiation of cardioprotective treatment in patients with muscular dystrophy. 5,6 Cardiomyopathy associated with muscular dystrophy has also been reported in female carriers of Duchenne and Becker muscular dystrophy.…”
Section: Introductionmentioning
confidence: 99%